Advertising as a Signal of Quality, A New Explanation - Paolo Garella; Claude Denys Fluet (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1995)
The present article provides a unied explanation for several phenomena related to advertising by rms. (i) Advertising without repeat purchase of the product, (ii) advertising from established brands, or post-introductory, (iii) simultaneous advertising from low and high quality rms, (iv) its persistence and pro-cyclicality. The explanation is original because it rests upon oligopolistic interaction. The analysis hinges upon two fundamental results. The rst is that advertising allows separation when a signal via prices only does not. The second is that purely dissipative advertising can be used to strategically deter entry. Hence, a link is established between entry deterrence and signaling.
Keywords: 330